Políticas de cobranza y su incidencia en la liquidez empresa La Tienda de Comercial Vásquez EIRL, Año 2020 - Pérez Tirado, Marilyn Esther (2022)
The present research work proposes that the collection policies affect the liquidity of the company La Tienda de Comercial Vásquez EIRL, year 2020 as a hypothesis that the collection policies positively affect the liquidity of the company La Tienda de Comercial Vásquez EIRL year 2020. Likewise As a general objective, to describe the incidence of collection policies on the liquidity of the company La Tienda de Comercial Vásquez EIRL in 2020, there are three specific objectives, which are: Establish the collection process and the collection policies of the company La Comercial Vásquez EIRL Store, Determine the liquidity level of the company La Tienda de Comercial Vásquez EIRL and Analyze the credit and collection policies in order to optimize the liquidity of the company La Tienda de Comercial Vásquez EIRL. Methodologically, the present investigation is of descriptive and non-experimental design, quantitative type and inductive method. The data collection technique was the survey, the documentary analysis, and the interview. The results determine that the company does not use established collection policies and that its collection management is not ideal. It is also determined that its liquidity levels are low and that, if it continues down this path, the company will not have enough liquidity to meet its short-term obligations. Finally, it is concluded that the collection policies have a significant impact on the liquidity of the company La Tienda de Comercial Vásquez EIRL in 2020.